Ability of Cronobacter sakazakii to adhesion and invasion AMGM5 cell line - Hayder A. Al-mandalawii; Luma Abdulhady Zwain; Estabraq A. Mahmoud (Iraqi Journal of Cancer and Medical Genetics, 2021)
Background: Cronobacter sakazakii is gram-negative bacteria , rod–shaped , facultative anaerobic the growth temperature range is 6–45 ° C . It is have many virulence factor such OmpA , flagella and extracellular glycoproteins help to adhesion and invasion of the host and found in macrophage to use invasion other organs in body .Aim of the study: Study ability of bacterial to adhesion on non-living surfaces (polystyrene) and living surfaces (brain cancer cell line) and its invasion , its cytotoxicity.Patients and methodsFifteenth of C. sakazakii were obtained from previous studies ( 5 infant formula , 5 spinal fluid and 5 bloods ) . Study of movement ability of bacteria , adhesion to polystyrene , adhesion to AMGM5 , invasion of AMGM5 and its cytotoxicity .Results: In this study , the number of C. sakazakii colony adherent to polystyrene plate more than 300 CFU for four isolated , while adhesion to (AMGM5 ) in dilution (1 : 10 and 1 : 100) were more than 300 CFU to four isolated , the number of invasioncolonies to AMGM5 were CSF5 ( 285 CFU ) , A1C ( 220 CFU ) , B1 ( <300 CFU ) , C1 ( 235 CFU ) . Cytotoxicity of C . sakazakii was 45. 81 % when using A1C isolate.Conclusion: C . sakazakii have the ability to movement , adhesion to polystyrene , adhesion and invasion to Cerebral glioblastomamultiforme and cytotoxic.